Morphofunctional cardiac changes in singleton and twin pregnancies: a longitudinal cohort study - Umazume, Takeshi; Yamada, Takahiro; Furuta, Itsuko; Iwano, Hiroyuki; Morikawa, Mamoru; Watari, Hidemichi; Minakami, Hisanori (BMC pregnancy and childbirth, 2020)
Background This study aimed to compare the echocardiographic changes and cardiac biomarkers between women with singleton and twin pregnancies. Methods From April 2014 to March 2016, this longitudinal cohort study invited pregnant women who were scheduled to give birth at Hokkaido University Hospital. We analyzed prospectively collected data on simultaneously determined echocardiographic parameters and blood cardiac markers of 44 women with singleton and 22 women with twin pregnancies. Furthermore, we tested the mixed-effect models for echocardiographic parameters and cardiac biomarkers. Results During the third trimester and immediately postpartum (within 1 week after childbirth), the mean left atrial volume index and brain natriuretic peptide (BNP) level were significantly higher in women with twin pregnancies than in those with singleton pregnancies. Women with twin pregnancies also had significantly smaller second-trimester inferior vena cava diameters and significantly higher third−trimester creatinine levels than those with singleton pregnancies. BNP positively correlated with the left atrial volume index (β = 0.49, p < 0.01) and the ratio of early diastolic transmitral to mitral annular velocity (E/e’) (β = 0.41, p < 0.01). At 1 month after childbirth in women with singleton pregnancies, BNP and N-terminal precursor protein BNP (NT-proBNP) fragments immediately postpartum negatively correlated with the later E/e’ (r = − 0.33, p = 0.02 and r = − 0.36, p < 0.01, respectively). Conclusions The intravascular cardiac load reached maximum within 1 week after childbirth and was greater in women with twin pregnancies than in those with singleton pregnancies. BNP/NT-proBNP significantly positively correlated with LA volume index and E/e’. In women with singleton pregnancies, BNP secreted immediately after childbirth might improve the diastolic functions 1 month after childbirth.